Effect of freezing period on the microbial and nutrient quality of pool barb, Puntius sophore from Dhaka city retail market, Bangladesh (Bangladesh Journal of Zoology, 2015)
The microbiological and nutrient quality of pool barb (Jatpunti), Puntius sophore collected from three local markets - Ananda bazaar, New Market and Polashi bazaar of Dhaka, Bangladesh were assessed. The investigation confirmed more or less higher microbial load in Ananda bazaar samples than the others. The microbial quality varied with market sources as total bacterial counts (TBC), total coliform counts (TCC) and faecal coliform counts (FCC) occurred in all storage period and that crossed the acceptable limit. All studied parameters except E. coli were significantly different at 7 days and 30 days of storage period and a significant difference (p < 0.05) was found in case of E. coli for all storage period where every 30 days storage showed one log reduction of bacterial count from every initial stage. The Salmonella shigella (SS) and Vibrio spp. were identified in all samples of studied local markets. An inverse relation was found between moisture and protein, moisture and fat, whereas the moisture content was increased after 30 days of freezing storage. This study concludes that the quality of P. sophore (Jatpunti) available in the studied three local markets of Dhaka city were neither satisfactory level nor to the standard for normal consumption.Bangladesh J. Zool. 41(1): 1-11, 2013